Tulasi a magical herb and a boon for management of oral submucous fibrosis: a clinical study - Madhulatha, G.; Vijayalaxmi, N.; Harshavardhan, T. (International Journal of Research in Medical Sciences, 2017)
Background: Plants are a good source of drugs in traditional and modern medicine. One among these plants is “tulasi” The queen of herbs” which is used in ayurveda for its diverse properties like antioxidant, analgesic, anti-inflammatory, antidiabetic, and others. It belongs to labiate family and is the most sacred and valued in traditional culture of India. AIMS of the study was to evaluate the efficacy of Tulasi in the treatment of OSMF. Methods: The study included 20 individuals, females and males of age group 20-50yrs who visited the outpatient department who were diagnosed clinically as having OSMF, categorized according to pindborg’s classification. Patients were asked to apply 500mg of Tulasi medicine paste (Tulasi powder mixed with glycerine) twice daily for 1month and were recalled for follow up every week for 1month. All the clinical parameters - mouth opening, burning sensation, pain with the lesion and others were evaluated and recorded in specially designed proforma. Results: Friedman test and wilcoxon signed rank test was used for statistical evaluation. Significant improvement with P value <0.05 was noticed in burning sensation, mouth opening and pain associated with the lesion. Conclusions: The study concludes that Tulasi can be used as a main treatment modality in the management of patients with OSMF.